Fiction film for Information Science: a study on thematic organization and representation approaches - Santos Sundstrom, Admeire da Silva [UNESP]; Ernesto de Moraes, Joao Batista [UNESP]; Albuuerque, Ana Cristina (Univ Federal Santa Catarina, 2019)
The audiovisual document is a material that integrates the image in movement and the sound in its essence, and it is contacted that this type of documentary is increasingly present in the interpersonal relations and, concomitantly, in the units of information. The audiovisual document addressed in this research is the fiction film. Thus, the question consist: how is Information Science addressing the subject matter of these materials? Thus, a bibliometric survey was carried out in a database with the objective of analyzing the literature on the thematic treatment modes of fiction films in the scope of Information Science, in order to understand how the thematic treatment of these materials has been occurring. The method is documentary and bibliometric. As a result, the low incidence of studies that approach the subject is highlighted; the influence of Cinema as a discipline in the processes of audiovisual indexing and the presence of a vast field for the development of researches.
Keywords: Audio-visual; Content analysis of fiction films; Fiction film; Film analysis; Thematic Treatment of Information